PERAN MANAJEMEN SDM DALAM LEMBAGA PENDIDIKAN UNTUK MENINGKATKAN MUTU PENDIDIK - Nurmalasari, Ita; Karimah , Dewi Zainul (Universitas Nurul Jadid, 2020)
This study examines the role of human resource management in improving the quality of educators. This research uses a qualitative approach with case study. This research site is in MTs Nu Ma'arif Kemiri, Purworejo Regency. The data collection technique used by researchers is interview observation. In this study, the object of research is the Role of Human Resources to Achieve Workforce Quality in MTs Nu Ma'arif Kemiri. Research data collection using descriptive observation, interview or qualitative methods. This interview observation study was conducted by lecturers and students of Islamic Education Management Study Program with student WK in MTs Nu Ma'arifKemiri. This activity aims to observe the Quality of Human Resources Workers conducted by MTs Nu Ma'arif Kemiri.